2021
DOI: 10.1155/2021/8811203
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Direct-Acting Antiviral Therapy on Thrombocytopenic Patients with Hepatitis C Virus-Related Chronic Liver Disease

Abstract: Background and Aims. Thrombocytopenia is a common complication in patients with chronic hepatitis C virus (HCV) that increases the risk of bleeding. We aimed to analyze the hematologic effects of the new direct-acting antiviral (DAA) therapy, particularly on the platelet count in chronic HCV-infected patients with thrombocytopenia. Patients and Methods. One hundred thrombocytopenic patients chronically infected with HCV were included in a prospective study. All patients were eligible for receiving anti-HCV tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
2
1
Order By: Relevance
“…The levels of liver enzymes decreased post-DAA, re ecting the resolution of HCV-related hepatic in ammation. Previous studies reported increases in hemoglobin levels, total leukocyte counts, and platelet counts after SVR [20][21][22], but these changes were not observed here. The hematological bene ts reported in prior studies could be secondary to improvements in liver brosis, portal hypertension, and anemia associated with chronic illness after SVR [23].…”
Section: Discussioncontrasting
confidence: 88%
“…The levels of liver enzymes decreased post-DAA, re ecting the resolution of HCV-related hepatic in ammation. Previous studies reported increases in hemoglobin levels, total leukocyte counts, and platelet counts after SVR [20][21][22], but these changes were not observed here. The hematological bene ts reported in prior studies could be secondary to improvements in liver brosis, portal hypertension, and anemia associated with chronic illness after SVR [23].…”
Section: Discussioncontrasting
confidence: 88%
“…Thrombocytopenia is a common complication in chronic HCV infection, causing an increased risk of bleeding[ 94 , 95 ]. The prevalence and severity of thrombocytopenia increase with the progression of liver disease and the development of hepatocellular damage and hepatic fibrosis[ 96 ].…”
Section: Extrahepatic Manifestations Of Chronic Hepatitis C Virus Inf...mentioning
confidence: 99%
“…Chen et al [ 97 ] found that 99.6% of chronic HCV infected patients with thrombocytopenia receiving DAA treatment achieved a SVR and thrombocytopenia improved significantly in 41.7% of them. Another study reported a highly effective and safe DAA regimen, with improvement of platelet count in 73% of thrombocytopenic patients, especially in mild to moderate stages of hepatic fibrosis[ 95 ].…”
Section: Extrahepatic Manifestations Of Chronic Hepatitis C Virus Inf...mentioning
confidence: 99%